Factors Associated with Budget Transparency: Evidence from the Municipalities of Chile (2021-2023) - Navarrete-Yanez, B (UNIV AUTONOMA CHILE, INST CHILENO ESTUDIOS MUNICIPALES, 2025)
Budgetary opacity is an indication of deficiencies in the integrity of local governance. Nevertheless, in Chile, there is still a lack of empirical studies examining the factors that influence it. Using indicators from the Council for Transparency, Social Observatory, Electoral Service, and National Municipal Information System, this study employs a fixed effects model and a logistic model to identify political, demographic, and political leadership variables associated with levels of budget transparency. The results indicate that municipalities with high poverty levels, lower rates of higher education, and higher debt perform worse, in contrast to those with female mayors, higher levels of higher education, larger populations, and a higher percentage of votes received by the mayor in the previous election.